Forced to be truthful. On the Essay on the lie and public communications in Kant's Philosophy of Right. - Rodríguez Ramírez, Jorge Omar (Con-Textos Kantianos. International Journal of Philosophy, 2023)
In the essay On a supposed right to lie from philanthropy, Kant discusses the unconditional duty of truthfulness, which has posed challenges for Kantian philosophy. This duty appears to compel individuals to always be truthful, regardless of whether their statements are public or private. I will refer to the interpretation that supports the obligation to be truthful in all statements as the extensive interpretation. I will demonstrate that this interpretation leads to inconsistencies with the Doctrine of Law. These inconsistencies can be resolved by adopting a restrictive interpretation of this duty, which states that the obligation of truthfulness only applies to public communications. If my interpretation is correct, it means that all public communications, whether from citizens or officials, must be truthful. Although my interpretation contradicts Kant's writings regarding the legal responsibility of lying, it is consistent not only with the Doctrine of Law but also with other texts where Kant discusses public communication.